Wearable solution for detecting knee and joint range of motion for arthritis patients - Li, ZhongTang (2014)
Based on some findings [1], arthritis is a disease which may cause the disability. It can cause arthritis patients to suffer from discomfort, pain, stiffness and fatigue. However the arthritis can’t be cured nowadays, but a lot of exercises or trainings can be done to minimize the impact of the arthritis. In the exercises, the detection of the joint motion is useful and helpful for arthritis patients. This project serves to provide wearable solutions to replicate knee motions of the arthritis patients. This model considers the knee joint as a 3 DOF joint. The model was used the Arduino and XBee modules to provide wireless transmission of the joint angle data, and used Processing software to achieve simulation. The experiment used varying signals from 2 pieces 9DOF Razor IMU sensors to detect and calculate the shin and thigh motions, then calculate the changed knee joint angles through Arduino based on the data from shin and thigh, and simulate the receiving angles of knee joint in Processing. Our model was able to achieve a normal range of motion of the knee joint, and was also able to continuously keep the changing knee angles into text file for other uses (for example, the data inside the text file can be used in the LabView to simulate etc.).